An evaluation of seasonal variations in footwear worn by adults with inflammatory arthritis: a cross-sectional observational study using a web-based survey - Brenton-Rule, Angela (J Foot Ankle Res, 2014)
BACKGROUND: Foot problems are common in adults with inflammatory arthritis and therapeutic footwear can be effective in managing arthritic foot problems. Accessing appropriate footwear has been identified as a major barrier, resulting in poor adherence to treatment plans involving footwear. Indeed, previous New Zealand based studies found that many people with rheumatoid arthritis and gout wore inappropriate footwear. However, these studies were conducted in a single teaching hospital during the New Zealand summer therefore the findings may not be representative of footwear styles worn elsewhere in New Zealand, or reflect the potential influence of seasonal climate changes. The aim of the study was to evaluate seasonal variations in footwear habits of people with inflammatory arthritic conditions in New Zealand. METHODS: A cross-sectional study design using a web-based survey. The survey questions were designed to elicit demographic and clinical information, features of importance when choosing footwear and seasonal footwear habits, including questions related to the provision of therapeutic footwear/orthoses and footwear experiences. RESULTS: One-hundred and ninety-seven participants responded who were predominantly women of European descent, aged between 46–65 years old, from the North Island of New Zealand. The majority of participants identified with having either rheumatoid arthritis (35%) and/or osteoarthritis (57%) and 68% reported established disease (>5 years duration). 18% of participants had been issued with therapeutic footwear. Walking and athletic shoes were the most frequently reported footwear type worn regardless of the time of year. In the summer, 42% reported wearing sandals most often. Comfort, fit and support were reported most frequently as the footwear features of greatest importance. Many participants reported difficulties with footwear (63%), getting hot feet in the summer (63%) and the need for a sandal which could accommodate a supportive insole (73%). CONCLUSIONS: Athletic and walking shoes were the most popular style of footwear reported regardless of seasonal variation. During the summer season people with inflammatory arthritis may wear sandals more frequently in order to accommodate disease-related foot deformity. Healthcare professionals and researchers should consider seasonal variation when recommending appropriate footwear, or conducting footwear studies in people with inflammatory arthritis, to reduce non-adherence to prescribed footwear.